CONCEPTS, ELEMENTS AND MAIN TASKS OF WORK ORGANIZATION AT THE ENTERPRISE - MAZUR, Dmytro; MAZUR, Alexander; MAZUR, Galina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the concepts, elements and main tasks of labor organization. The concept of "labor organization" is defined, which is a way of combining performers with means of correction for the implementation of the labor process and the achievement of the goal of the activity. It was determined that an effective system of work organization at an industrial enterprise is possible only with the coordinated work of all elements. A graphic model of labor organization is proposed. It is also determined that the organization of work can be interpreted as a system that begins with the emergence of a problem or need, then a goal is formed, which is realized due to the interrelationships between such elements as: labor force, working conditions, tools and objects of work. After the interaction of these components, the product of activity and the completion of the process is formed - the result of work. The work organization system is considered, which is an effective tool for the organization of work at the enterprise and is the factor that affects it, realizing the rationalization and coordination of labor and material resources in time and space. The article also examines how external and internal factors affect the organization of work. The theoretical base of labor organization depends on external factors. Internal ones include the following: working conditions, lighting, noise, vibration, etc. All these factors exerting an important influence on the activity of the enterprise determine the main methods of labor organization and the effectiveness of their application. An analysis of the researches of various scientists was made, and it was found that the division and cooperation of labor, the creation of safe working conditions are the most important elements of labor organization.
Keywords: labor organization; theoretical basis; external factors; rationalization and coordination of labor resources; internal factors; labor productivity; production capacity